1986
DOI: 10.1007/bf00580675
|View full text |Cite
|
Sign up to set email alerts
|

Reflex prolongation of stage I of expiration

Abstract: Experiments were performed on anesthetized cats to test the theory that the interval between phrenic bursts is comprised of two phases, stage I and stage II of expiration. Evidence that these represent two separate neural phases of the central respiratory rhythm was provided by the extent to which stage duration is controlled individually when tested by superior laryngeal, vagus and carotid sinus nerve stimulation. Membrane potential trajectories of bulbar postinspiratory neurons were used to identify the timi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
79
1
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 26 publications
18
79
1
1
Order By: Relevance
“…This pattern of response is consistent with the observations of Gilbey et al (1984). In their studies involving intracellular and extracellular recordings from the cardiac vagal motoneurones, they showed that the neurones did not fire during the ramp phase of phrenic nerve activity corresponding to inspiration, but were active during stage I expiration (post-inspiration) and during stage II expiration when the phrenic nerve was silent (Richter, 1982;Remmers, Richter, Ballantyne, Bainton & Klein, 1986). Maximum values of the membrane potential (-50 to -60 mV) during inspiration were followed by depolarization at the onset of stage I expiration when they discharged some action potentials.…”
Section: Of This Paper)supporting
confidence: 83%
“…This pattern of response is consistent with the observations of Gilbey et al (1984). In their studies involving intracellular and extracellular recordings from the cardiac vagal motoneurones, they showed that the neurones did not fire during the ramp phase of phrenic nerve activity corresponding to inspiration, but were active during stage I expiration (post-inspiration) and during stage II expiration when the phrenic nerve was silent (Richter, 1982;Remmers, Richter, Ballantyne, Bainton & Klein, 1986). Maximum values of the membrane potential (-50 to -60 mV) during inspiration were followed by depolarization at the onset of stage I expiration when they discharged some action potentials.…”
Section: Of This Paper)supporting
confidence: 83%
“…This hypothesis has been supported by data obtained from decerebrate cats. These data strongly support the concept of a two-phase theory of expiration (Richter, 1982; Remmers, Richter, Ballantyne, Bainton & Klein. 1986).…”
Section: Introductionsupporting
confidence: 70%
“…As has been reported by others (Gesell & Hamilton, 1941;Lawson, 1981Lawson, , 1982Remmers et al 1986), stimulation of the superior laryngeal nerve could result in prolongations of the expiratory phase. Two patterns of stimulation were used in this study.…”
Section: Prolongations Of Neural Expirationmentioning
confidence: 62%
See 1 more Smart Citation
“…Neurophysiologically expiration has been divided into early and late phases (24,36,(43)(44)(45)(46). The firing of geniohyoid I/E-MU during expiration did not appear to be strongly modulated by the two phases of expiration.…”
Section: Introductionmentioning
confidence: 97%